10
Step-by-step explanation:
first what is 10 take away 2 is 8 then 10 take away 2 is 8 + 2 equals 10 8 + 2 equals 10 so that's how I got the answer 10
This what it should look like. did you need the steps or no ?
Answer:
Rate of change = -12
Step-by-step explanation:
y − 3 = −12(x + 4)
Expanding, we have;
y - 3 = -12x - 48
y = -12x - 48 + 3
y = -12x - 45
Now, formula for rate of change is;
Rate of change = (y(x + h) - y)/h
y(x + h) is; y = -12(x + h) - 45
This gives;
Rate of change = (-12(x + h) - 45 + 12x + 45)/h
Rate of change = (-12x - 12h - 45 + 12x + 45)/h
Rate of change = -12h/h
Rate of change = -12
Answer:
Well i mean i know i am is college but i have not learned it yet. sorry :(
Step-by-step explanation: